2015
DOI: 10.1038/cr.2015.30
|View full text |Cite
|
Sign up to set email alerts
|

ERK kinase phosphorylates and destabilizes the tumor suppressor FBW7 in pancreatic cancer

Abstract: F-box and WD repeat domain-containing 7 (FBW7) is the substrate recognition component of the Skp1-Cul1-F-box (SCF) ubiquitin ligase complex and functions as a major tumor suppressor by targeting various oncoproteins for degradation. Genomic deletion or mutation of FBW7 has frequently been identified in many human cancers but not in pancreatic ductal adenocarcinoma. Thus it is important to know how the tumor suppressive function of FBW7 is impaired in pancreatic cancer. In this study, we first observed that low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
116
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 118 publications
(127 citation statements)
references
References 47 publications
(64 reference statements)
5
116
0
Order By: Relevance
“…Among these substrates, HIF1a, PGC1a, and c-Myc are well-known regulators of metabolism. We previously reported that the expression of c-Myc decreased dramatically when FBW7 was overexpressed in pancreatic cancer (8). However, no change in the expression of PGC1a or HIF1a was observed upon FBW7 upregulation in pancreatic cancer.…”
Section: Txnip Is a Negative Regulator Of Glucose Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these substrates, HIF1a, PGC1a, and c-Myc are well-known regulators of metabolism. We previously reported that the expression of c-Myc decreased dramatically when FBW7 was overexpressed in pancreatic cancer (8). However, no change in the expression of PGC1a or HIF1a was observed upon FBW7 upregulation in pancreatic cancer.…”
Section: Txnip Is a Negative Regulator Of Glucose Metabolismmentioning
confidence: 99%
“…Emerging evidence has shown that FBW7 is also regulated by multiple upstream genes, such as p53, Pin1, Hes-5, and Numb4, as well as by miRNAs (7). We previously reported that fewer than 2% of pancreatic cancer samples harbored FBW7 mutations, according to sequencing analysis (8). Furthermore, with mass spectrometry analysis, we detected that ERK kinase phosphorylated FBW7 at the T205 site, which resulted in destabilization of FBW7 in pancreatic cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Immunohistochemical staining of paraffin-embedded tissues with antibodies for MUC16, phosphorylation of ERK (p-ERK), c-Myc, and FBW7 were performed and scored to determine the proteins expression according to standard procedures described previously (23).…”
Section: Immunohistochemical Stainingmentioning
confidence: 99%
“…For example, 1 study has reported that a p53‐FBW7‐Aurora B axis, which identified FBW7 as a transcriptional target of p53 21. Another study found that FBW7 could be phosphorylated and destabilized by ERK kinase 25. More intriguingly, just before this work was finished, Yang's team discovered a novel circ‐FBW7 in glioma cells, which is able to antagonize the inhibitory effect of USP28 on FBW7α so as to degrade c‐Myc 26.…”
Section: Discussionmentioning
confidence: 99%